Effect of Water Transport on Swelling and Stresses in PFSA Membranes. Issue 1 (16th December 2014) - Khattra, N. S.; Santare, M. H.; Karlsson, A. M.; Schmiedel, T.; Busby, F. C.
Abstract The mechanical durability of membranes used in proton exchange membrane fuel cells (PEMFC) is directly linked to the stresses that evolve in the membrane during fuel cell operation. The stresses are primarily induced due to the swelling of the membrane as it absorbs water, within the mechanical constraints in the fuel cell assembly. Thus, in order to predict the membrane stresses, the water content in the perfluorosulphonic acid (PFSA) membranes is determined numerically via three different absorption models based on experimentally determined water uptake data from the literature. Two models are based on a single, humidity‐dependent Fickian transport coefficient for the bulk PFSA membrane. In the third, two transport properties are modeled to account for a possible difference in transport resistance between the bulk membrane and the outer surface. The membrane sorption behaviors characterized from these three models are then independently incorporated in a representative fuel cell finite element model and subjected to a standard relative humidity (RH) protocol designed for measuring mechanical durability of PEMFCs. The results show that the sorption behavior has a significant effect on the membrane stresses and therefore, may impact the lifetime of the membrane.